The southward shift of hurricane genesis over the northern Atlantic Ocean - Xi Cao; Renguang Wu; Xianling Jiang; Yifeng Dai; Pengfei Wang; Lei Zhou; Liang Wu; Difei Deng; Ying Sun; Shangfeng Chen; Kaiming Hu; Zhibiao Wang; et al. (npj Climate and Atmospheric Science)
Abstract The hurricane, with maximum wind speed over 64 kts, is among the most terrible calamities over the northern Atlantic (NATL). Previous studies identified a poleward migration of tropical cyclone (TC) genesis over the Pacific Ocean, but the shift over the NATL is statistically insignificant. The present study detects a robust southward migration in the genesis latitude of NATL TCs that later reach hurricane strength after 1979, which is consistent with a growth in hurricane frequency in the southern part (10°-20°N) of NATL. This increasing trend of hurricane frequency is intimately attributable to the decreasing vertical shear of zonal wind, resulting from a decreasing north-south temperature gradient. The reduced north-south temperature gradient is primarily caused by greater warming trend in tropospheric temperature in the subtropics, driven by intensified static stability. The present research suggests a potential increase in the hazards confronted by low-latitude islands and coastal nations in Northern America.